Цунами: [роман] / Николай Задорнов - Задорнов Николай Павлович (Сибириада, 2022)
Экземпляры: ф.16 (20230419) / Инвентарный номер: 63391 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: З-15 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-44